8x-7=6x+23

Simple and best practice solution for 8x-7=6x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-7=6x+23 equation:


Simplifying
8x + -7 = 6x + 23

Reorder the terms:
-7 + 8x = 6x + 23

Reorder the terms:
-7 + 8x = 23 + 6x

Solving
-7 + 8x = 23 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-7 + 8x + -6x = 23 + 6x + -6x

Combine like terms: 8x + -6x = 2x
-7 + 2x = 23 + 6x + -6x

Combine like terms: 6x + -6x = 0
-7 + 2x = 23 + 0
-7 + 2x = 23

Add '7' to each side of the equation.
-7 + 7 + 2x = 23 + 7

Combine like terms: -7 + 7 = 0
0 + 2x = 23 + 7
2x = 23 + 7

Combine like terms: 23 + 7 = 30
2x = 30

Divide each side by '2'.
x = 15

Simplifying
x = 15

See similar equations:

| 2(x-3)=2*x | | 2w-6w=56 | | 5x+6+6x+5=50 | | -3(h+5)+2=4(h+6) | | 4a-4a^2=0 | | -88-12X=7-2x-6 | | R+20=50 | | -x^4-2x^2+1=0 | | 11+4p=4+3p | | 5-9n+5n=27-82 | | 11Z-17=105 | | -2q-3q=18 | | 7x^2=104 | | log(2x-5)=1 | | 7+3d-5=-1+2-12+d | | 7+6x=4(x-5)+7 | | 2k^2-19k+10=0 | | 4t-t-5=2t-8 | | 15.4+3.5=-1.2h-6 | | 8(3b+3)=5b+5 | | 7s+2s-7s=8 | | -9x-6=4x+33 | | (5y+3)(2y+7)=11y-10 | | x^7-3x^6=0 | | Q+10=25 | | 4x-(9x+3)=7x-27 | | 4(c+1)=16 | | 6Z-5=37 | | .79x+230=43777 | | 16=80 | | 3x+15-6x=-(-x+1) | | [k-10]=30 |

Equations solver categories